The Aesthetic of Traditional Lurik in Socio-Cultural Context / E. S.Handayani - Handayani, E. S. (2016)
Lurik motif is filled with meaning, but in fact the formation of weaving of Lurik are not as beautiful as the meaning of its tone. In the background is formulated problem regarding: 1) the existence of Lurik; 2) traditional motif; 3) Klaten traditional Lurik aesthetic value, Aesthetic element that are analyzed through AAM Djelantik Aesthetic Analysis. Traditional Lurik motifs idea come from flora and fauna as well as the Motifs of Lurik that depicts symbolically the circumstances, the beauty and wonders of nature; (4) Lurik aesthetic value resulting from striping, the diversity of color that produce the motif give happiness to wearer and its lovers.